Analisis Probabilitas Keruntuhan Pada Lereng Tanah Residual Dengan Variasi Sudut Kemiringan Lereng - Thiya Fianti; Eko Andi Suryo; Harimurti Harimurti (Rekayasa Sipil, 2018)
Slope is (part of) the side of a hill or mountain. Slope stability became the main concern while working on a construction project, especially on road/highway project. Slope stability determined by soil parameters which include: physical & mechanical behavior of the soil, ground water level, rock mass structure, etc. Because there is an uncertainty on parameters value in the slope design, causing the slope vulnerable, it needs a concept such as probability analysis to find the stability of the slope. Probability analysis using Monte Carlo method involved a few parameters such as unit weight, cohesion and friction angle. Soil and Slope Geometry data were obtain from prior research. In this analysis there are three trials conducted with various slope angle along with similar material. The result will show a safety factor and failure probability percentage. From this analysis, it can be concluded that the steeper the slope, the lower safety factor number will be shown. The contrary result applied on probability of failure, the steeper the slope, the bigger probability of failure for soil material will occur.